(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Sesame oil is a plant-derived source of biologically active substances and contains fatty acids, phenolic compounds, and natural antioxidants. Classical and modern medical literature describes its anti-inflammatory, antioxidant, cardioprotective, and metabolism-regulating properties. This article presents an overview of the pharmacological effects of sesame oil based on the analysis of reliable scientific and educational sources. Particular attention is given to the cellular mechanisms of action of its biologically active components, as well as its role as a preventive and supportive therapeutic agent. The presented data indicate that sesame oil can be considered a promising natural product in the fields of pharmacology and preventive medicine.